Unravelling the chemical design of spin-crossover nanoparticles based on iron(ii)–triazole coordination polymers: towards a control of the spin transition - Giménez-Marqués, Mónica (Royal Society of Chemistry, 2015)

(untitled) (J Mater Chem C Mater Opt Electron Devices)
A systematic study of the key synthetic parameters that control the growth of spin-crossover (SCO) nanoparticles (NPs) using the reverse micelle technique has been undertaken in the system [Fe(Htrz)(2)(trz)](BF(4))·H(2)O, (Htrz = 1,2,4-triazole). This has permitted us to modulate the physical properties of the NPs in a controlled and reproducible manner. In particular, a control over the size of the NPs (in the range 4 to 16 nm) has been achieved by varying the water to surfactant molar ratio. The consequences of this size variation on the cooperativity of the spin transition are discussed. Finally, this approach has been extended to the chemical alloy [Fe(Htrz)(2.95)(NH(2)trz)(0.05)](ClO(4))(2) in order to prepare NPs exhibiting a cooperative and hysteretic spin transition centred closer to room temperature.